Inclination towards agriculture among rural youth in Malaysia - Abdullah, Farah Adila; Abu Samah, Bahaman; Othman, Jamilah (TextRoad Publication, 2012)
Globally, agriculture has been admitted as one of the important sectors and the similar setting can be found in Malaysia. Government has never stopped in placing their effort to further improve this sector and it can be proven through the establishment of number of high impact agriculture projects. As the sector has well developed, nonetheless, the ageing agriculture community in Malaysia has raised concerns among the related parties and such issue has driven this paper to its main objective which is to explore the inclination of the younger generation particularly the youth towards involvement in agriculture. This paper is exploratory in nature where data were gained through literature and document analyses. Based on the findings, it can be concluded that most of the youth have a positive perception about agriculture but only few of them are involved directly in this field.